The experimental arrangement and preliminary results of search for light neutron clusters in 235u nuclei decay; NUCLEUS - 2021. Nuclear Physics and Elementary Particle Physics. Nuclear Physics Technologies - Dudkin G. N. Gennadiy Nikolaevich (2021, 2021)
Title screen